Utilization of Butterfly Pea (Clitoria ternatea) Plant in Rice to Lower Glucose Levels - Jocelyn Louise; Victor Christian Kaharso; Natasya Hermawan; Nerissa Arviana Tristanto (International Journal of Food Sciences and Nutrition Innovations, 2025)
Background of study: The increasing prevalence of diabetes and other glucose-related metabolic disorders has sparked a growing interest in functional foods that can help regulate blood sugar levels. Among staple foods, rice plays a crucial role in the diets of billions of people, particularly in Asia. However, white rice has a GI, contributing to rapid spikes in blood glucose levels after consumption. This presents a health challenge for individuals at risk of or currently managing diabetes. Recent studies suggest that anthocyanins from butterfly pea may inhibit enzymes involved in carbohydrate digestion (e.g., α-amylase and α-glucosidase), thereby slowing glucose absorption in the bloodstream. Additionally, incorporating butterfly pea extracts or powders into rice may not only reduce its GI but also enhance its nutritional value and sensory appeal, offering both functional and aesthetic benefits. Aims and scope of paper: The primary aim of this paper is to investigate the potential of butterfly pea as a natural functional ingredient in rice-based products to reduce postprandial blood glucose levels. Specifically, the study seeks to evaluate the effects of incorporating butterfly pea extracts or powders into rice formulations on glycemic response, nutritional content, and overall product acceptability. This paper focuses on the functional food application of Butterfly Pea in rice, with an emphasis on reducing glycemic impact. It encompasses phytochemical analysis, food formulation, nutritional evaluation, and potential health benefits. Methods: This review aims to evaluate and compile scientific evidence to substantiate the functional claims associated with butterfly pea. Therefore, it is crucial to systematically gather and analyze research findings that explore its functional properties based on empirical scientific investigations. Result: We reviewed the existing literature related the butterfly pea. Several studies reported that butterfly pea has numerous functional properties, such as inhibitory activity against α-amylase and α-glucosidase enzymes. Conclusion: The incorporation of Butterfly Pea into rice formulations presents a promising strategy for developing functional foods with a reduced glycemic impact. The study demonstrated that butterfly pea is rich in bioactive compounds particularly anthocyanins and flavonoids that contribute to its inhibitory effects on carbohydrate-digesting enzymes and its potential to lower postprandial glucose levels.